Strategi Komunikasi Kampanye Puskesmas Kaliwungu Dalam Menyukseskan Program Poskestren (Pos Kesehatan Pesantren) - Maulidina Zahra Nabila; Hamid Arifin (Universitas Sebelas Maret (UNS), 2024)
Poskestren was established with the aim of establishing the independence of boarding schools in implementing Clean and Healthy Living Behavior (PHBS). This is motivated by the many negative stigmas regarding hygiene that is not maintained in the boarding school environment. Similar to the stigma of boarding schools in several regions in Indonesia, boarding schools in Kaliwungu are also known for being shabby, crowded, poorly maintained, and only eat what they can without paying attention to the nutrition contained in them. In fact, the sanitation condition is also alarming. Therefore, Kaliwungu Community Health Center as a government agency responsible for public health in Kaliwungu Sub-district took the initiative to establish Poskestren as a means of educating the boarding school residents and persuading them to implement PHBS, so that the negative stigma obtained by the boarding school regarding the cleanliness of its environment will gradually disappear and be replaced with a positive stigma that the boarding school is a clean, comfortable, and pleasant place to learn. This research analyzes the campaign communication strategy by using Arifin Anwar's communication strategy steps. The research used a qualitative approach and descriptive research type by conducting in-depth interviews and documentation studies obtained from sources and the internet. The results showed that Kaliwungu Health Center conducted a campaign communication strategy in the success of Poskestren. There are several stages of campaign communication strategy conducted by Kaliwungu Health Center in the success of Poskestren program, namely 1) Knowing the audience by understanding how the nature and behavior of the boarding school residents so that the chances of achieving communication success will be higher 2) Arranging the message in an educative and persuasive way to invite the boarding school to succeed Poskestren and be able to apply clean and healthy living behavior in daily life. 3) Applying methods by using repetition (redundancy), informative, educational, and persuasive methods, 4) Selection and use of media by providing counseling and using media in the form of pamphlets or posters as a visual companion.